Interpolation in the Notational Plane: A Case Study - Neelameghan, A.; Bhattacharya, Ganesh; Gupta, A. K. (Journal of Information and Knowledge, 2002)
Examines the cases where homonymous (CN) may arise by the use of the Emptying Digits of the CC Notational System. Discusses the advantages and disadvantages of using each of three different devices for interpolation in an array.